2003
DOI: 10.1159/000068855
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of Pelvic Pouch following Restorative Proctocolectomy: Report of a Case and Review of the Literature

Abstract: One of the possible long-term complications following an ileoanal pouch procedure is the development of malignancy in the mucosa of the rectal stump. Only 10 such cases have been reported so far. We report the case of a 23-year-old male who had ulcerative colitis with high-grade dysplasia and underwent an ileoanal pouch procedure. He was found to have a malignancy in the rectal stump 5 years after surgery. The malignancy presented with symptoms of refractory pouchitis. Pouch excision was performed. The risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…35,41 These patients with dysplasia or cancer of the ATZ typically had a precolectomy diagnosis of dysplasia or cancer. [34][35][36] In patients with persistent dysplasia, mucosectomy, perianal pouch advancement, neoileal pouch-anal anastomosis, or pouch excision have been recommended. 36,45 There is scanty data on clinical features and management of polyps of the pouch.…”
Section: Discussionmentioning
confidence: 99%
“…35,41 These patients with dysplasia or cancer of the ATZ typically had a precolectomy diagnosis of dysplasia or cancer. [34][35][36] In patients with persistent dysplasia, mucosectomy, perianal pouch advancement, neoileal pouch-anal anastomosis, or pouch excision have been recommended. 36,45 There is scanty data on clinical features and management of polyps of the pouch.…”
Section: Discussionmentioning
confidence: 99%
“…This colonic metaplasia is presumably an adaptation to the new environmental condition because the ileal pouch may in part substitute for the functions of the large intestine 7. Furthermore, Gullberg et al has reported on the development of severe mucosal atrophy in the pouch with risk of neoplastic transformation8; in addition, there have also been case reports of adenocarcinoma in the ileal mucosa of the pouch 8‐11…”
mentioning
confidence: 99%
“…Eighteen reported cases have surfaced during the past 25 years, all but two in association with CUC. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] This is the first report of this complication occurring in the setting of IC. Although most cases have been diagnosed within a few years of RPC, pouch-related adenocarcinomas have been reported at 12, 6 14, 7 and 18 11 years after index surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Of 14 cases [5][6][7][9][10][11][12][13]16,[19][20][21] in which pathologic data are available, all but one 8 contained cancer, dysplasia or both in the colorectum. In the present case, as in others reported, the tumor probably originated outside the pouch and grew inward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation